Performance of clinical and histological prognostic scores for kidney survival in ANCA-associated vasculitis - Sandino-Bermúdez, Marlon J; Hernández-Andrade, Adriana; Hinojosa-Azaola, Andrea; Martín-Nares, Eduardo; Mejía-Vilet, Juan M (Rheumatology (Oxford, England), 2025)
Integrating clinical and histological parameters into prognostic scores may enhance the prediction of progression to kidney failure in anti-neutrophil cytoplasm antibodies-associated vasculitis (AAV). This study aimed to evaluate the prognostic performance of histological classifications and scoring systems for kidney survival in AAV. This retrospective cohort study included 101 AAV patients with kidney involvement diagnosed by biopsy and followed for ≥12 months. The main outcome was the time to kidney failure. The prognostic performance of each histological and prognostic score was evaluated using Harrell's C statistic and Akaike's Information Criteria. Among the 101 patients, 37 progressed to kidney failure over a median follow-up of 75 months (IQR 39-123). The Harrell's C statistic was 0.702 (0.620-0.784), 0.606 (0.473-0.738), 0.801 (0.736-0.867), 0.782 (0.706-0.858) and 0.817 (0.749-0.885) for the EUVAS/Berden classification, Mayo Clinic Chronicity Score, Percentage of ANCA Crescentic Score (PACS), ANCA renal risk score (ARRS), and the improved ANCA kidney risk score (AKRiS), respectively. The AKRiS best discriminated the risk of kidney failure progression among subgroups. The AKRiS performance decreased with longer follow-up intervals. Adding the peak estimated glomerular filtration rate attained post-therapy improved the AKRiS performance at all follow-up intervals. Kidney relapses precipitated kidney failure in 71% of cases that progressed after the first year of follow-up. The novel AKRiS enhances the prediction of kidney failure in AAV with kidney involvement. As the prognostic yield of AKRiS decreases over time, a second calculation of AKRiS, including post-therapy kidney function, may improve its long-term performance.